Ultrasound-guided paravertebral blockade reduced perioperative opioids requirement in pancreatic resection: A randomized controlled trial - Han, Ye; Dai, Yuanqiang; Shi, Yaping; Zhang, Xiaoxiu; Xia, Boyang; Ji, Qiufang; Yu, Xiya; Bian, Jinjun; Xu, Tao (Frontiers in Surgery, 2022)
Background Perioperative opioid use for pain control has been found to be associated with side effects and adverse prognosis. In this study, we hypothesized that paravertebral block could reduce the consumption of opioids during pancreatic resection surgery. Methods We conducted a prospective, randomized trial. Patients with resectable pancreatic cancer were randomly assigned to one of the two groups: those who received bilateral paravertebral block combined with general anesthesia [bilateral paravertebral blockade (PTB) group] or those who received only general anesthesia (Control group). The primary endpoint was the perioperative consumption of opioids (sufentanil and remifentanil). The main secondary endpoints were pain scores, complications, and serum cytokine levels. Results A total of 153 patients were enrolled in the study and 119 cases were analyzed. Compared to the control group, patients in PTB patients had significantly lower perioperative (30.81 vs. 56.17 µg), and intraoperative (9.58 vs. 33.67 µg) doses of sufentanil (both p < 0.001). Numerical rating scale scores of pain were comparable between the two groups. No statistical differences in complications were detected. Conclusion Bilateral paravertebral block combined with general anesthesia reduced the perioperative consumption of opioids by 45%. Registration number ChiCTR1800020291 (available on http://www.chictr.org.cn/).